Differences in Career Decision Making Self Efficacy (CDMSE) Between Men and Women in Generation Z - Wulandari, Annisa Silvia; Purnama, Diana Septi (International Journal Labs, 2024)
The current phenomenon shows that teenagers often need more confidence in making career decisions. This study aimed to identify differences in the level of Career Decision Making Self-Efficacy (CDMSE) between male and female students in Senior High School (SMA). The type of research used was quantitative and used a comparative method. The population of this study was 640 students in grades XI and XII in high school. The sample of this study was 200 students taken using a random sampling technique. The method used in collecting data was a questionnaire. The instrument used was the CDMSES-SF scale developed by N.E. Betz. The data analysis technique used in this study was non-parametric analysis with the Mann-Whitney test. The results obtained from the data analysis showed significant differences in the level of CDMSE between male and female students. Male students have higher CDMSE than female students. For male students, special attention is needed on the planning and goal selection aspects, while for female students, it is on the planning aspect. These results suggest that male and female students need different approaches to career guidance, especially in planning and goal selection.